Walt disney's cinderella (Grolier Danbury, Connecticut, 1995)
When Cinderella's cruel stepmother forbids her from attending the Royal Ball, she gets unexpected help from her mice friends and her Fairy Godmother. Cinderella attends the ball as a mysterious guest and dances with the prince